Exploring the relationship between religiosity, ethnocentrism and corporate image: young Muslim consumers perspective - Haque, A. K. M. Ahasanul; Rahman, Sabbir; Yasmin, Farzana (World Business Institute, Australia, 2012)
This paper aims to examine how young Malay Muslim consumers differs their idea about religiosity; ethnocentrism and corporate image before they intend to purchase any foreign made goods and services. This research also explores the relationship between religiosity, ethnocentrism and corporate image towards the perception of purchasing foreign goods by the young Muslim consumers in Malaysia. Total of 600 (350 males and 250 females) young consumers response were collected from public and private Universities as well as shopping mall intercept by using convenient sampling procedure. This research had conducted three stages of data analysis for instance: exploratory factor analysis; confirmatory factor analysis and structural equation modeling to test the hypothesis. Among all the variables, corporate image and ethnocentrism behavior played the most significant role on the perception of young Muslim consumer’s before purchasing foreign made products. A major limitation exists in this research of its self-reported nature of survey which was used in the study. Further research should include some assessments such as observations or other-reported survey of the young consumer’s behavior towards purchasing foreign made products. This study provides a useful source of information for global marketers to understand the perception of Malaysian young consumers’ towards foreign made products.